Peningkatan Kualitas Pelayanan Publik Melalui Implementasi E-Government di Bali - Dian Putri Agustina (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
E-Government is one of the information technology public services provided by the government to improve performance, efficiency, accountability, and public trust. However, there are still many public complaints about alleged administrative fraud in public services. The purpose of this study is to determine the relationship between digital transformation through the introduction of e-government and improving the quality of public services in Bali and which of these two factors affect the quality of public services through the introduction of e-government in Bali. This study was conducted on people in Bali Province who have used online public services. Data were collected through an online questionnaire instrument with a sample of 70 respondents. The analysis technique uses PLS analysis. The results of the analysis show that the role of the community, ICT and E-Government have a significant effect on the quality of public services in the Province of Bali. E-Government has an important role in improving the quality of public services optimally in the Province of Bali.